Method of initiating the bullk discharge with fast electron beam in gas; Proceedings of the XIth International Conference on Phenomena in Ionized Gases, Prague, 1973 - Bychkov Yu. I. (1973, 1973)
В фонде НТБ ТПУ отсутствует